Development of Learning Modules on Circles Using Augmented Reality for Eighth-Grade Students - Diana Sefti; Dodik Mulyono; Nur Fitriyana (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
This research aims to develop an augmented reality-assisted circle learning module for 8th-grade students at SMP Negeri 4 Lubuklinggau that is valid, practical, and has potential effects. The study employs the 4-D development model (define, design, develop, and disseminate). The augmented reality-assisted circle learning module is deemed valid based on language validator scoring 0.85, media validator scoring 0.87, and content validator scoring 0.86. The summary of validator test results shows high scores with an average of 0.88. Practicality results from teachers show 89.33 and from small group student practicality are 92.85, indicating that the module scores high with an average of 86.26, thus deemed very practical. The learning module demonstrates potential effects on student learning outcomes, where 30 students successfully completed with a percentage of 93.75, categorized as successfully completing the Minimum Completion Criteria (KKM) set at 70.